CHARACTER EDUCATION MODELS FOR MI TEACHERS: A NARRATIVE REVIEW - Nur Innayah Ganjarjati; Dwi Purbaningrum (Penelitian dan Pengembangan Ilmu, 2026)
Character education based on religious moderation has become a strategic agenda in Madrasah Ibtidaiyah (Islamic elementary schools) to address the challenges of information disruption and social polarization. This study aims to synthesize effective character education models for Madrasah Ibtidaiyah teachers through a narrative review approach of literature published over the last decade (2016–2026). Thematic analysis identified three dominant models: (1) the Role Modeling Model, which positions teachers as uswatun hasanah (exemplary role models); (2) the Curriculum Integration Model, which incorporates character values into all components of the learning process; and (3) the Culture-Building Model, which relies on social habituation and a supportive school climate. The findings indicate that although these three models are effective, their implementation is often constrained by administrative burdens, limited resources, and the pressures of the digital environment. The study concludes that character development requires a holistic approach that integrates all three models while strengthening teacher capacity and providing systemic support. This review recommends the integration of technology-based character education to ensure the effective internalization of wasathiyah (religious moderation) values among students in the digital era. The findings are expected to serve as a reference for policymakers in strengthening the role of madrasahs as adaptive institutions for character education.